Formulasi Krim Griseofulvin Dan Uji Penetrasi Menggunakan Sel Difusi Franz - Auzal Halim; Iin Indah Sari; Maria Dona Octavia (Jurnal Farmasi Higea, 2012)
Griseofulvin cream formulation and it’s penetration test using Franzs difusion cell has been done. This cream formulation was using two different types of base cream, such as water/oil (w/o) and  oil/water (o/w) base cream type. The vertical type cells of Franz difusion cells, was used for the penetration test and it’s quantity determination was done by using spectrophotometry methods. The result  showed,  that griseofulvin cream with water/oil (w/o) base has the highest of the griseofulvin penetration quantity. The griseofulvin penetration quantity and it’s capacity of penetrating toward water/oil (w/o) and  oil/water (o/w) base are 7,447  µg/mL and 18,54%, then  5,724 µg/mL and 14,39% respectively for 90 minutes periods time. It showed that the cream type can influence the griseofulvin penetration from it’s base. From both cream types, water/oil (w/o) type gives better penetration than oil/water (o/w) cream.